A hive of activity: realigning the figure of the bee in the mead-making network of Exeter Book Riddle 27. Issue 4 (December 2017) - Price, Helen
Abstract In dialogue with the recent movement toward more ecomaterialist analyses of environment in early medieval literature, the following essay engages with the methodology of Actor Network Theory to explore the network of interactions constructed inExeter Book Riddle 27, usually solved as 'mead.' While the riddle clearly presents the processes of mead making and consuming, the figure of the bee appears to be strangely absent in the riddle's construction of this mead-making process. Fulfilling Bruno Latour's proclamation to 'follow the actors, ' this essay argues that the behaviors, drives and characteristics of the bee are present in the interactions which take place between named actants and the riddle text as a whole. The riddle form opens up the mead-making/consuming network(s), emphasizing the bee actant's presence in and influence on this transfer of energy.